HLA-B genotype and Escherichia coli association in Iraqi patients with reactive arthritis - Galeef, Emad Resen; Salloom, Dunya Fareed (Iraqi Journal of Science, 2022)
Reactive arthritis (ReA) has been as joint developing after infection, it belongs to spongylo arthritis (SpA). The etiology of this disease was multi factorial, the combination between genetic and environmental factors for triggering this disease. This study included 75 Iraqi Arab patients and 39 healthy control. Urine samples and blood were collected from each subject. The results showed that Escherichia coli bacteria (E. coli) was isolated from 32% of urine samples. HLA-B*27 allele frequencies was higher in ReA patients infected with E. coli. This lead to suggest that E. coli may be trigger factor in ReA patients with UTI which had HLA-B*27 positive.